(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The scientific article provides an overview of the law enforcement practice under the Project Finance Factory program with an emphasis on problematic aspects and difficulties in implementing certain provisions. The composition of the regulatory framework that forms the basis of the Project Finance Factory program is disclosed, and its transformation is traced. A review of economic literature is provided indicating the opinions of scientists on the implementation of the Project Finance Factory program, highlighting controversial issues and aspects that require further development and improvement.